Organizational Culture in a Cross-Cultural Context - Thomas Kalkschmidt (Journal of Applied Leadership and Management, 2013)
Do similar national cultures support the transfer of organizational culture from a company's headquarters to its subsidiaries?
Keywords: 650; OCAI; semi structured interview; transfer of organizational culture